2000
DOI: 10.1016/s0022-5347(05)66929-7
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer in Men Age 50 Years or Younger:: A Review of the Department of Defense Center for Prostate Disease Research Multicenter Prostate Cancer Database

Abstract: These data suggest that patients in the PSA era who underwent radical prostatectomy and were age 50 years or younger have a more favorable disease-free outcome compared to older men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 22 publications
4
57
1
3
Order By: Relevance
“…4,5 However, clinical findings to support this notion have to date been mixed. [6][7][8][9][10][11][12][13][14] Independent of the prognosis of early versus late-life onset PCa, it is possible that the biological pathways that drive this disease differ by age. However, to date, there have been no studies examining the similarities and differences in the prognostic drivers of PCa in different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, clinical findings to support this notion have to date been mixed. [6][7][8][9][10][11][12][13][14] Independent of the prognosis of early versus late-life onset PCa, it is possible that the biological pathways that drive this disease differ by age. However, to date, there have been no studies examining the similarities and differences in the prognostic drivers of PCa in different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Therefore, the use of lower PSA cutoffs may detect prostate cancer more frequently in its curable stages. 5 As few as 25% of men with a PSA level of 4-10 ng ml À1 have prostate cancer, and up to 25% of men with a PSA of o4 ng ml À1 will have prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…2 Early diagnosis of prostate cancer has been of great value, as younger age is an independent predictor of better prognosis. 3,4 Moreover, the use of lower PSA cutoffs may detect prostate cancer more frequently in its curable stages. 5 Patients aged less than 50 years were studied before for early cancer detection.…”
Section: Introduction and Aim Of The Workmentioning
confidence: 99%
“…In their study of 477 men who underwent RP, Smith et al [18] found that younger patients (less than 50 years old) had a better disease-free survival probability (logrank P = 0.010). On multivariate Cox regression analysis, age remained a significant prognostic factor (P = 0.033).…”
Section: The Influence Of Age On Survival Outcomesmentioning
confidence: 99%
“…On multivariate Cox regression analysis, age remained a significant prognostic factor (P = 0.033). They concluded that patients younger than 50 years old have a more favorable disease-free outcome [18]. Obek et al [19] studied 489 patients with localized prostate cancer.…”
Section: The Influence Of Age On Survival Outcomesmentioning
confidence: 99%